ANALISIS KINERJA KEUANGAN PADA KOPERASI SIMPAN PINJAM “WANITA KARYA LANGA” KECAMATAN BAJAWA KABUPATEN NGADA - Ma’a, Petrasia Yunita; Soleiman, Iriany Dewi; Banda, Falentina Lucia (Jurnal Riset Ilmu Akuntansi, 2023)
The purpose of this study was to determine the financial performance of the Karya Langa Women's Savings and Loans Cooperative, Bajawa District, Ngada Regency in 2019-2021. This type of research is Descriptive Research. This research was conducted at the Karya Langa Women's Savings and Loans Cooperative, Bajawa District, Ngada Regency with the sample being the balance sheet report and remaining business results for 2019, 2020 and 2021. the results of the analysis in the balance sheet report and remaining operating results for 2019-2021 are: 1. The current ratio value from 2019 reached 227% with very good criteria, then in 2020 it reached 226% with very good criteria, and in 2021 it reached 159% with pretty good criteria. Thus the cooperative's liquidity for three years in terms of the current ratio can be declared healthy in meeting short-term debt and current assets owned by the cooperative. 2. The debt ratio in 2019 was 76.10% with unfavorable criteria; in 2020 it is 75.25% with not good criteria; and in 2021 it is 72.17% with unfavorable criteria. Thus the solvency of the cooperative for three years in terms of the debt ratio can be declared not yet solvable in fulfilling its debts. 3. The value of return on equity in 2019 was 6.77% with unfavorable criteria; in 2020 it is 1.26% with bad criteria and in 2021 it is 1.28% with bad criteria. Thus the profitability of cooperatives for the last three years has not been profitable in producing SHU.